Flypaper Effect pada Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), dan Dana Alokasi Khusus (DAK) terhadap Belanja Daerah pada Pemerintah Kabupaten/Kota di Provinsi Kalimantan Selatan (2009 – 2013) - Wia Rizqi Amalia; Wahyudin Nor; M Nordiansyah (Jurnal Akuntansi dan Bisnis, 2015)
This study was aimed to demonstrate the effect of local revenue (PAD), general allocation fund (DAU), and special allocation fund (DAK) to the local government expenditure, and also demonstrate empirically whether the effect of the DAU and DAK to the local government expenditure are larger than the effect of PAD to the local government expenditure in the district/city of South Kalimantan Province in 2009-2013 period. Data analysis method used in this research is descriptive statistical analysis and multiple linear regression analysis using the SPSS (Statistics Product and Service Solutions) version 17. Before performing data analysis, first tested the classical assumption of normality test, multicollinearity, autocorrelation, and heteroscedasticity test. The results showed that: (1) the PAD does not affect the local government expenditure, (2) the DAU affect the local government expenditure, (3) the DAK affect the local government expenditure, and (4) the coefficient of the DAU and the DAK is greater than the value of the coefficient of PAD, and both significantly influence the local government expenditure. This indicates that there has been a flypaper effect on local government expenditure in the districts / cities at South Kalimantan Province in 2009-2013 periods.